2015
DOI: 10.3126/ijasbt.v3i3.12915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality Protein Maize and Drought Tolerant Maize in Far Western Hills of Nepal

Abstract: The coordinated varietal trial of quality protein maize was carried out in research station of regional agricultural research station, Doti during 2011/12 and 2012/13. A total of fourteen entries including standard and local checks were included in the experiment of both years. Out of tested entries of the year 2011/12, S99TLYQ-A produced the highest grain yield (2814 kg/ha) followed by SO3TLYQ-AB-01 (2765 kg/ha) and SO3TLYQ-AB-02 (2293 kg/ha). MSTATC software was used in data analysis. Flowering days, plant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
3
1
0
Order By: Relevance
“…The possible reason for the observed differences in grain yield among the maize genotypes under the same station trials (locations) was due to their variation in their genetic makeup. These results are in line with those of Prasai et al (2015), who observed considerable genotypic variability among various QPM genotypes in hill regions of Nepal.…”
Section: Resultssupporting
confidence: 92%
“…The possible reason for the observed differences in grain yield among the maize genotypes under the same station trials (locations) was due to their variation in their genetic makeup. These results are in line with those of Prasai et al (2015), who observed considerable genotypic variability among various QPM genotypes in hill regions of Nepal.…”
Section: Resultssupporting
confidence: 92%
“…The yield remains statically similar 3.28 t/ha for irrigating everyday with the amount 50% of ET whereas the drastically reduction of yield has found in the treatment T8 (0.85 t/ha) to treatment T10 (0.31 t/ha) as a lowest yield. The yield observed in this experiment is quite similar to the yield determined by Prasai et al (2015) for drought tolerant maze genotype.…”
Section: Effects Of Water Stress On Yieldsupporting
confidence: 82%
“…However all the tested genotypes were significantly higher grain yield than the Farmers' Local Variety. Also, Prasai et al (2015) indicated similar results.…”
Section: A-yield Yield Components and Protein (%)supporting
confidence: 69%